Quantifying the variability of bipolar voltage amplitude with sensing angle in residual conduction isthmuses in atrial scar. (19th May 2022) - Merino, JL; Kim, S; Relan, J; Castrejon Castrejon, S; Sanroman, M; Escobar Cervantes, C; Martinez Cossiani, M; Carton, A
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: The angle between the activation wavefront and bipole may conceal the conduction isthmus in conventional bipolar voltage mapping, but the extent of variability of electrogram (EGM) voltage amplitude with directional changes has not been quantified. Purpose: Using a well-defined model of discrete atrial conduction, we sought to use Omnipolar Technology (OT) to assess variability of voltage amplitude as a function of sensing angle, in sites of residual conduction and scar tissue. Methods: During redo pulmonary vein isolation (PVI) procedures, baseline voltage maps were acquired during coronary sinus pacing (500 ms) using a rectangular 16-pole catheter (HD Grid). During retrospective analysis with OT research software, all EGM's ≤1 cm radius from the site of PVI were classified as GAP (vs No-GAP; Panel A) The variability of voltage amplitude (OT-ΔV) with sensing angle (θ) was computed as the difference between the maximum and minimum voltages (OT-Vmax - OT-Vmin), in both GAP and No-GAP subregions (Panels A & B). Results: 23 GAP sites were identified in 12 of 15 consecutive patients studied. 3464 EGM's (1386 GAP vs 2078 No-GAP) were analyzed. Global mean OT-ΔV was 0.46±0.80 mV. GAP regions showed significantly (P<0.0001) higher OT-ΔV as compared with No-GAP regions (0.80±1.03 mV vs 0.24±0.47 mV respectively; Panel C) The mean Δθ angle for OT-ΔV was similar in both GAP and No-GAP regions (88.6±11.3° vs 88.0±13.6°, P=0.1; Panel D). Conclusion: The variability of voltage amplitude as a function of bipole orientation can be significant, especially in GAP regions (0.80±1.03 mV). (2) OT-ΔV holds promise for identification of residual conduction within atrial scar tissue.